(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study aimed to investigate the effect of Trikatu-Triphala Churna Pradhaman Nasya in the management of Kaphaj Pratishaya (sinusitis). The study involved 30 patients with sinusitis who received Pradhaman Nasya treatment with a mixture of Trikatu and Triphala Churna. The patients were assessed before and after the treatment, and the data were analyzed statistically. The study found that the treatment led to significant improvement in the clinical condition of the patients, including relief of symptoms such as nasal discharge, sneezing, nasal obstruction, headache, voice change, and cough. The treatment was well-tolerated and showed promising results in the management of Kaphaj Pratishaya. This simple and cost-effective remedy may provide an alternative treatment option for sinusitis. Further research is warranted to validate these findings and explore the potential mechanisms of action of Trikatu-Triphala Churna Pradhaman Nasya in sinusitis management.